Análisis del Desempeño entre Dapper y Entity Framework, caso Aplicativo: Sistema de Buenas Prácticas en Empresas Turísticas de Riobamba - Silva Rivera, Jayron Omar (2019)
Currently, tourism is taking on new horizons, demand from consumers is increasing, and tourism service providers are developing new programs to extend tourist activity. The GADM Riobamba in agreement with the UNACH defined "Good Practices" that must be met by service providers to obtain a quality badge awarded by the municipality. This process required a web system that allows automation to help carry out the self-assessment, evaluation and decision-making process to improve the services offered by the different establishments in Riobamba city. To develop of the system, a comparative analysis between DAPPER and ENTITY FRAMEWORK was carried out to evaluate the performance efficiency of the data access abstraction layer. The indicators were established according to ISO / IEC 25010 standards where a model for the evaluation of software quality is established, these being: temporal behavior, resource utilization and capacity, using two tools; 1) Jmeter with the PerfMon extension and 2) System.Diagnostics library with the TimeSpan and PerformanceCounter methods which allowed capturing the response times and resource used of the previously established parameters. With the results obtained by measuring the metrics in the two prototypes, it was determined that DAPPER improves the performance efficiency in the data access abstraction layer, implemented the ORM in the Tourism Good Practices System of the Riobamba canton.